2017
DOI: 10.1016/j.ymgme.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to clinic recommendations among patients with phenylketonuria in the United States

Abstract: Clinic recommendations of target blood Phe concentrations in the US are now stricter compared to prior years, and largely reflect recent guidelines by the American College of Medical Genetics and Genomics (Vockley et al., 2014). Adherence to recommended Phe concentrations remains suboptimal, especially in older patients. However, despite remaining above the guidelines, actual blood Phe concentrations in adolescents and adults are lower than those reported in the past (Walter et al., 2002; Freehauf et al., 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
124
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 18 publications
5
124
0
1
Order By: Relevance
“…Several studies demonstrate that many adults with PKU have elevated blood Phe concentrations, indicating that blood Phe control for this population is a significant challenge and current treatment strategies are not efficacious for all patients [7][8][9][10]. An estimated 88% of adults with PKU are unable to adhere to Phe-restriction long term, and even in those reporting adherence, blood Phe concentrations above recommended ranges commonly occur [4,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrate that many adults with PKU have elevated blood Phe concentrations, indicating that blood Phe control for this population is a significant challenge and current treatment strategies are not efficacious for all patients [7][8][9][10]. An estimated 88% of adults with PKU are unable to adhere to Phe-restriction long term, and even in those reporting adherence, blood Phe concentrations above recommended ranges commonly occur [4,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 88% of adults with PKU are unable to adhere to Phe-restriction long term, and even in those reporting adherence, blood Phe concentrations above recommended ranges commonly occur [4,[10][11][12][13]. Sapropterin is currently the only pharmacologic agent approved to treat adults with PKU, though it is only effective in patients with residual PAH activity; in clinical trials, only 20%-56% of patients with PKU responded to sapropterin, as measured by a reduction in blood Phe concentration [2,6,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of participants (75%) were noncompliant as evidenced by plasma PHE levels >360 μmol/L, which reduced the size of the compliant subgroup for our analysis. Unfortunately, high numbers of noncompliance with plasma PHE and diet requirements, particularly among adolescents and adults, are common in the PKU medical population . Another limitation was that plasma tryptophan could not be calculated into the sum of plasma LNAA concentrations in 14 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, high numbers of noncompliance with plasma PHE and diet requirements, particularly among adolescents and adults, are common in the PKU medical population. [31][32][33][34] Another limitation was that plasma tryptophan could not be calculated into the sum of plasma LNAA concentrations in 14 cases. This may have affected the sum of the plasma LNAA concentration values and the significance of associations in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…4 Acceptance of a PKU diagnosis by patients and subsequent adherence to the low natural protein diet is well documented in the literature to be difficult. [4][5][6][7][8][9] A 2016 publication by Witalis et al 5 documented that 63% of children aged between 2 and 10 years and 49% of parents struggled to accept a diagnosis of PKU. A later publication by Witalis et al (2017) further investigating the knowledge and attitudes of parents and children reported that 22% of parents and 30% of children had a sense of helplessness with the daily complexities of trying to implement the low natural protein diet.…”
Section: Introductionmentioning
confidence: 99%